2019
DOI: 10.1136/heartjnl-2019-315381
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients likely to be readmitted after transcatheter aortic valve replacement

Abstract: Hospital readmission following transcatheter aortic valve replacement (TAVR) contributes considerably to the costs of care. Readmission rates following TAVR have been reported to be as high as 17.4% at 30 days and 53.2% at 1 year. Patient and procedural factors predict an increased likelihood of readmission including non-transfemoral access, acute and chronic kidney impairment, chronic lung disease, left ventricular systolic dysfunction, atrial fibrillation, major bleeding and prolonged index hospitalisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(61 reference statements)
2
5
0
Order By: Relevance
“…Similar work in this area has been done by Goldsweig et al. (2020) 21 and Li et al. (2021) 22 Goldsweig et al.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similar work in this area has been done by Goldsweig et al. (2020) 21 and Li et al. (2021) 22 Goldsweig et al.…”
Section: Discussionsupporting
confidence: 71%
“…The ability to stratify patients according to readmission risk is necessary because initiatives aimed at lowering rehospitalization rates may be more successful when targeted toward those patients who are most at risk. 20 Similar work in this area has been done by Goldsweig et al (2020) 21 and Li et al (2021) 22 Goldsweig et al 21 conducted a rapid review to identify predictors for post-TAVI readmission. They reported on 10 studies and 24 unique predictors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Lastly, early and late rehospital readmissions that affect post-TAVR mortality were not recorded in this study. 28,29 Our study suggests that sex-related differences exist after TAVR by measuring echocardiographic parameters. Women had better LVEF and LVMI than men.…”
Section: Discussionmentioning
confidence: 75%
“…In a study by Kamioka et al, 28 next‐day discharge showed similar 30‐day and better 1‐year clinical outcomes when compared to those with longer hospital stay, indicating patient safety as the number one advantage. In order to reach this goal, thorough pre‐procedural work‐up and information to the patient prepares for an early discharge 27 as well as taking the frailty and comorbidities of the patient into consideration 29 …”
Section: Discussionmentioning
confidence: 99%